Study of the technological process of mechanical processing of parts with shaped surfaces in milling machines - Gafurov, Akmaljon Mavlonjonovich; Khamidjonov, Abdumalik Khasanjon ogli (Science and Education, 2023)
In modern mechanical engineering, the development of a technological process for processing stamping forms on shaped surfaces remains the most important task of today. Before processing the shaped surfaces, it will be necessary to study the working surfaces of the stamping molds. This article describes methods for determining the geometric parameters of the surface when processing stamping forms on shaped surfaces, in particular, the drawing structures of the cutting zone of shaped surfaces, the penetration of the cutter into the cutting zone and data on the conditions of editing in the cutting zone.